Re-reading Weber, or: The three fields for the analysis of power in international relations - Stefano Guzzini (Danish Institute for International Studies (DIIS), 2007)
This new Working Paper argues that power analysis is at the crossroads of three different fields which follow a certain autonomous logic. First, there is a field of political theory which is concerned with the nature of the `polity' in which questions of the organisation of (organised) violence and of the common good, as well as questions of freedom, are paramount. It is where power stands for `government' or `governance' and political order, as well as personal `autonomy'. The logic in the field of explanatory theories is to think power in terms of a theory of action mainly and a theory of domination subsequently. Here, power is searched for the explanation of behaviour and the outcomes of social action. It is here where power is thought in terms of `agency', `influence' or prevalence, if not `cause'. In the praxeological field, politics is the `art of the possible' in which collective violence is not antithetical but fundamental to politics. Power is furthermore connected to the idea of state sovereignty and the discourse of the reason of state, including an ethics of responsibility. The three fields are exemplified by Weber's analysis of power which came at a time when all three logics had acquired a sufficient independence of each other, and yet still stood relatively connected.
Keywords: 330